Survey of E-scooter users in Vienna: Who they are and how they ride. (December 2020) - Laa, Barbara; Leth, Ulrich
Abstract: In many cities around the world, electric (e-)scooters have emerged as a new means of transportation. They are often advertised as supporting modal shift towards more sustainable transportation and as a tool for enabling more equity in mobility. However, the environmental impact depends on how they are used and what kinds of trips they replace. Integration of e-scooters into urban transport systems also implicates discussions on fair road space allocation. In our study, we assess the socio-economic profiles and usage patterns of e-scooter users in Vienna, Austria. We differentiate between two basic groups of e-scooter users (renters and owners) and apply two different methods. Firstly, based on an online survey, we examine the age, gender and education of e-scooter users and we look into which kinds of trips (commuting, shopping or leisure) and which other means of transportation are replaced by e-scooter trips. Secondly, we analyse data from field observations at cycle paths in Vienna in order to determine the share of e-scooter riders and their gender distribution. We find that e-scooter users are more likely to be young, male, highly educated and residents of Vienna. According to the survey, there are considerable differences in usage between owners of private scooters and users of sharing schemes. Whereas in both groups, e-scooter trips mostly replace walking and public transport as a mode, e-scooter owners also show a considerable mode-shift from private car trips. These results implicate that e-scooter riders are additional users of cycling infrastructure. This puts further pressure on the current allocation of road space, which provides little space for active modes of transport. We conclude that city policies should address this competitive relationship adequately by allocating more space to safe and convenient cycling infrastructure and traffic-calmed zones. This could not only help ease the current challenges due to e-scooters but also provide better conditions for walking and cycling and thereby at the same time contribute to a more sustainable and equitable urban transport system.